Chemical characteristics of nectarine genitors used for breeding program in Romania - Ivascu, A. (International Journal of Horticultural Science, 2002)
The geographic location of Bucharest area, the nature of its soil and its climate offer remarkably favourable conditions for nectarine growing, with juicy and well flavoured fruit, good for fresh consumption and processing.The five years' investigation (1996-2000) has helped to identify some nectarine cultivars and hybrids (NJN 58, ARK 165, ARK 139, Morton, ARK 107, Romamer I, ARK 125, Firebrite) with exceptional fruit quality (dry matter content, titratable acidity, vitamin C content, overall sugar, and amount of pectic substances).Dry matter content varied over the three years from 8.3 to 18.5% (NJN 68), meanwhile titratable acidity varied between 0.26 and 1.08% (Romamer I). Sugar / acidity ratio was within the limits of 8.6 and 36.5 (Nectared 7). Nectarines have high vitamin C content, over 10 mg/100g (Fairlane, NJN 67, Regina, Harko), glucides were found in Firebrite, Romamer I varieties and NJN 21, CIR1T127, HFSR3P4, HNA hybrids.Some cultivars have been recommended for planting in this southern area of Romania (Crimsongold, ARK 125, Harko, Hardyred, ARK 134), others used as quality genitors (ARK 85, Nectared 7, NJN 21, ARK 21, ARK 134, Fantasia) in breeding projects.